A Pengembangan Instrumen Penilaian Tiga Ranah Berbasis HOTS Pada Mata Pelajaran PAI-BP di SMP - Rizky Rahayu; Fuji Pratami; Ali Jusrin Pohan (At Turots: Jurnal Pendidikan Islam, 2023)
The purpose of this study was to find out the description of the PAI-BP learning assessment process before and after, the validity and practicality of developing HOTS-based three-domain assessment instruments in class VIII SMPN 2 Panyabungan on the material "Respect and Obedience to Parents and Teachers”. The method used in this research is research and development with the 4D development model (define, design, develop, disseminate). Data was obtained through needs analysis instruments, validity instruments, and practicality instruments. The three HOTS-based assessment instruments in class VIII SMPN 2 Panyabungan were declared valid by the three validators with a percentage score on the construction aspect of 83% being very valid, the material aspect being 81% being very valid, and the language aspect being 84% being very valid. The overall validation got a score of 82% very valid from the three validators. Based on the results of the questionnaire analysis of students' responses to the practicality of using the developed assessment instrument, it was found that this assessment instrument was very practical to use in learning assessment with an average acquisition of 90% and from the teacher's response questionnaire with an average score of 85% with very practical information from the three domains that had been developed. Based on the results of the validity and practicality that have been carried out by researchers on the three HOTS-based assessment instruments in PAI-BP subjects in class VIII SMPN 2 Panyabungan, they can be used in the learning assessment process.